2002
DOI: 10.1029/2001gl013562
|View full text |Cite
|
Sign up to set email alerts
|

Deserts: Can they be the potential suppliers of bioavailable iron?

Abstract: The temporal and spatial variability of bioavailable iron delivered to the ocean may be controlled via in‐cloud photochemical reduction of desert dust, assisted by the impact of oxalate released by fungi in the desert soil. The basic process in the photochemical production of bioavailable iron through decarboxylation reaction involves simultaneous action of oxalate released by the fungus encapsulated in a cloud droplet, above some threshold solar radiation. Therefore, diurnal and latitudinal variations in sola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 10 publications
5
36
0
2
Order By: Relevance
“…For our data the low EF (< 10) for all studied elements and depths indicates significant contribution from a crustal source, as previously documented in sediment trap samples in the northwestern Mediterranean by Roussiez et al (2012). It is well documented that the EMS is occasionally influenced by Sahara dust events from northern Africa, containing natural crustal material (Guerzoni et al, 1999;Herut et al, 2005;Jickells, 1995;Ridame and Guieu, 2002;Saydam and Senyuva, 2002).…”
Section: Sources Of Natural and Anthropogenic Compounds In The Deep Isupporting
confidence: 82%
“…For our data the low EF (< 10) for all studied elements and depths indicates significant contribution from a crustal source, as previously documented in sediment trap samples in the northwestern Mediterranean by Roussiez et al (2012). It is well documented that the EMS is occasionally influenced by Sahara dust events from northern Africa, containing natural crustal material (Guerzoni et al, 1999;Herut et al, 2005;Jickells, 1995;Ridame and Guieu, 2002;Saydam and Senyuva, 2002).…”
Section: Sources Of Natural and Anthropogenic Compounds In The Deep Isupporting
confidence: 82%
“…The atmospheric chemical processing of iron occurs in clouds because they provide a relatively high acidic environment. Observations confirm the relatively high solubility of the iron found in precipitation (e.g., Saydam and Senyuva, 2002). Concerning the solar radiation influence, Zhu et al (1997) observed higher values of soluble iron during the daytime.…”
Section: Iron Solubility and Atmospheric Processingsupporting
confidence: 68%
“…It has been suggested that during atmospheric transport, photoreduction of Fe (III), which is stable and relatively insoluble, produces Fe (II), a biologically available and soluble species (e.g., Graedel et al 1986, Duce andTindale 1991). Saydam and Senyuva (2002) propose that oxalate released by fungi in desert dust facilitates photoreduction of Fe (III). Complexation of Fe (II and III) with organic ligands (Butler 1998) with clay minerals in the aerosol acts to stabilize the iron in a bioavailable form.…”
Section: Nutrient Influx and Biogeochemical Effectsmentioning
confidence: 99%